Odpowiedzi

2009-10-15T20:48:38+02:00
X-1 x-y 1
___ _ ___ = - ___
3 2 2
x + y = 3 --->> x = 3 - y

3-y-1 3-y-y 1
_____ _ ____ = - ___
3 2 2

2-y 3-2y 1
___ _ ____ = - ___
3 2 2

4-2y 9-6y 3
___ _ ____ = - ___
6 6 6

4y - 2
_____ = 0
6
4y - 2 = 0

y= 0,5

x = 3 - y

x= 2,5

1 1 1
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2009-10-15T21:01:21+02:00
X-y x-y
____ - _____ = - ½\6
3 2

x + y = 3

2(x-y)-3(x-y)=-3
x+y=3

2x-2y-3x+3y=-3
x+y=3

-x+y=-3
x+y=3
_________
2y=0
y=0

-x+0=-3/÷(-1)
x=3

x=3
y=0